Batasan Penegak Hukum Dalam Mengakses Data Elektronik Pribadi - Eunike Briliantin Rahantoknam (Universitas Widya Gama Malang, 2023)
Personal data contains important information about that person. In Indonesia, there is still no beginning regarding the limitations of law enforcement in accessing personal data in the form of electronics. Only an explanation of some laws and regulations, but nothing in detail. Personal data is a person's privacy, not something that everyone can know, because it is personal, an example of personal data is ID cards. KTP is important for Indonesian citizens, because they declare themselves to be Indonesian citizens. Of course, with the development of the times, everything uses electronics, even ID cards are in electronic form, namely E-KTP. That way, people can access someone's personal data, including law enforcers who can't access someone's personal data not all of them, of course there are conditions if they want to access someone's personal data. Likewise, there is no clear provision regarding the limitations of access to personal data based on Permenkominfo 5/20 concerning Private Scope Electronic System Operators. Several statutory regulations that explain, namely the 1945 Constitution, Law Number 11 of 2008 jo. Law no. 19 of 2016 concerning information and electronic transactions and Permenkominfo 5/20. It is necessary to know that law enforcers in accessing a person's personal data must have a court decision.